To solve for x, we need to isolate the x term on one side of the equation.
Starting with the equation x/3 - 9 = 6, we can first add 9 to both sides of the equation to eliminate the constant term on the left side:
(x/3) - 9 + 9 = 6 + 9
This simplifies to:
x/3 = 15
Next, we can multiply both sides of the equation by 3 to isolate the x term:
3 * (x/3) = 3 * 15
This simplifies to:
x = 45
Therefore, the solution to the equation x/3 - 9 = 6 is x = 45.
What is the solution of the equation x/3 − 9= 6 solving for x ?
7 answers
Randall needs to solve the equation 5x + 8 = 63 . His first mathematical operation used to isolate x is subtraction. Which value will he apply it to?
To isolate x in the equation 5x + 8 = 63, Randall will need to use subtraction to eliminate the constant term of 8 on the left side.
His first mathematical operation will be subtracting 8 from both sides of the equation:
5x + 8 - 8 = 63 - 8
This simplifies to:
5x = 55
Therefore, Randall will apply subtraction to the constant term of 8.
His first mathematical operation will be subtracting 8 from both sides of the equation:
5x + 8 - 8 = 63 - 8
This simplifies to:
5x = 55
Therefore, Randall will apply subtraction to the constant term of 8.
Marion is solving the equation 9x − 6 = 12 . As a first step, she adds 6 to both sides of the equation. In the next step, by what value does each side need to be divided?
After Marion adds 6 to both sides of the equation 9x − 6 = 12, the equation becomes:
9x − 6 + 6 = 12 + 6
This simplifies to:
9x = 18
In the next step, Marion needs to divide each side of the equation by the coefficient of x, which is 9.
Therefore, each side needs to be divided by 9.
9x − 6 + 6 = 12 + 6
This simplifies to:
9x = 18
In the next step, Marion needs to divide each side of the equation by the coefficient of x, which is 9.
Therefore, each side needs to be divided by 9.
Beejal is solving the equation y/7 − 3 = 39
To solve the equation y/7 - 3 = 39, Beejal will need to perform the following steps:
1. Start by adding 3 to both sides of the equation to eliminate the constant term on the left side:
y/7 - 3 + 3 = 39 + 3
This simplifies to y/7 = 42.
2. To isolate y, Beejal needs to multiply both sides of the equation by 7 to eliminate the fraction:
7 * (y/7) = 7 * 42
This simplifies to y = 294.
Therefore, the solution to the equation y/7 - 3 = 39 is y = 294.
1. Start by adding 3 to both sides of the equation to eliminate the constant term on the left side:
y/7 - 3 + 3 = 39 + 3
This simplifies to y/7 = 42.
2. To isolate y, Beejal needs to multiply both sides of the equation by 7 to eliminate the fraction:
7 * (y/7) = 7 * 42
This simplifies to y = 294.
Therefore, the solution to the equation y/7 - 3 = 39 is y = 294.